2013
DOI: 10.1097/aln.0b013e31828ce817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthesia and Surgery for Congenital Heart Disease on the Vitamin D Status of Infants and Children

Abstract: Most CHD patients are vitamin-D deficient postoperatively due to low preoperative levels and a significant intraoperative decline. Interventional studies will be required to determine whether prevention of postoperative vitamin D deficiency improves outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 44 publications
3
69
0
4
Order By: Relevance
“…Using the widely accepted cutoff of ,20 mg/dl to diagnose 25(OH)D deficiency, we reported recently that .40% of critically ill children in our hospital were deficient. Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)supporting
confidence: 75%
See 1 more Smart Citation
“…Using the widely accepted cutoff of ,20 mg/dl to diagnose 25(OH)D deficiency, we reported recently that .40% of critically ill children in our hospital were deficient. Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)supporting
confidence: 75%
“…Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26). Despite the rapidly increasing volume of evidence linking 25(OH)D deficiency with ICU morbidity and mortality over the past 10 years (1-4, 6-8, 10, 11, 27, 28), the question of whether vitamin D repletion will improve clinical outcomes in critical illness remains unclear.…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)supporting
confidence: 75%
“…Many other studies also showed significant decrease in serum vitD levels as a result of CPB effect in the immediate postoperative period. On the contrary, the control group showed rise in the mean value of serum vitD levels in the immediate post CPB period in sample C compared with sample B. Riad et al, 39 McNally et al, 40 Graham et al, 41 and Krishnan et al 42 studied the effect of CPB on serum vitamin D levels which is compared in ►Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…32 A study by McNally and colleagues determined vitamin D status in children undergoing congenital heart surgery. 32 They found that 42% of patients were vitamin D deficient preoperatively and 86% of the same patients were deficient postoperatively. 32 There was a significant intraoperative decline, which appeared to coincide with cardiopulmonary bypass.…”
Section: Vitamin D and Calciummentioning
confidence: 99%
“…32 There was a significant intraoperative decline, which appeared to coincide with cardiopulmonary bypass. 32 Lower postoperative levels were associated with increased fluid requirements, ventilation days, and catecholamine requirements with heart dysfunction and other markers of organ dysfunction. 32 Although this study is limited by heterogeneity and small sample size, it suggests that current vitamin D recommendations are inadequate for the preoperative congenital heart disease patient and that preoperative and postoperative repletion may have the potential to change hospital outcomes.…”
Section: Vitamin D and Calciummentioning
confidence: 99%